2014
DOI: 10.1378/chest.13-2538
|View full text |Cite
|
Sign up to set email alerts
|

Macrolide/Azalide Therapy for Nodular/Bronchiectatic Mycobacterium avium Complex Lung Disease

Abstract: Current guidelines for macrolide/azalide-based therapies for NB MAC lung disease result in favorable microbiologic outcomes for most patients without promotion of macrolide resistance. Intermittent therapy is effective and significantly better tolerated than daily therapy. Microbiologic recurrences during or after therapy are common and most often due to reinfection MAC genotypes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
215
6
5

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 302 publications
(237 citation statements)
references
References 37 publications
11
215
6
5
Order By: Relevance
“…6,22 MAC isolates were identified using AccuProbe (Hologic Gen-Probe). Mab isolates were identifi ed to species and subspecies using sequencing of region 5 of the rpo b gene and polymerase chain reaction restriction fragment length analysis of an approximately 441 base pairs heat shock protein gene ( hsp ) 23 using two restriction endonucleases, BstE II and Hae III, as described previously.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…6,22 MAC isolates were identified using AccuProbe (Hologic Gen-Probe). Mab isolates were identifi ed to species and subspecies using sequencing of region 5 of the rpo b gene and polymerase chain reaction restriction fragment length analysis of an approximately 441 base pairs heat shock protein gene ( hsp ) 23 using two restriction endonucleases, BstE II and Hae III, as described previously.…”
Section: Methodsmentioning
confidence: 99%
“…Semiquantitative AFB smear and culture results for each submitted clinical specimen during and aft er therapy were recorded as described previously ( Table 1 ) . 6,22 Macrolide/azalide susceptibilities for MAC used broth microdilution according to contemporary guidelines. 19 Clarithromycin was used as the class drug for both macrolide and azalide susceptibility.…”
Section: Methodsmentioning
confidence: 99%
“…53 Patients given daily medication were more likely to change to three times weekly regimens due to GI side eff ects, but overall treatment success was achieved in 84% of patients. No macrolide resistance developed in any patients.…”
Section: Choice Of Macrolidementioning
confidence: 99%
“…Also, intermittent treatment was well tolerated and required fewer regimen modifications than daily treatment [16,17]. Owing to these patients' susceptibility to NTM-PD, recurrence rates remain high [17]. In a small fibro-cavitary MAC-PD cohort in The Netherlands, 57% of patients achieved prolonged culture conversion; addition of clofazimine and amikacin in patients with most severe disease yielded similar outcomes [18].…”
mentioning
confidence: 99%
“…In patients with nodular-bronchiectatic MAC-PD, groups from the USA and South Korea have shown that intermittent treatment with the rifamycin-ethambutol-macrolide regimen is highly successful, leading to prolonged culture conversion in 70-85% of the patients. Also, intermittent treatment was well tolerated and required fewer regimen modifications than daily treatment [16,17]. Owing to these patients' susceptibility to NTM-PD, recurrence rates remain high [17].…”
mentioning
confidence: 99%